Filter-free, junctionless structures for color sensing. Issue 38 (15th September 2016) - Lin, Keng-Te; Chen, Hsuen-Li; Lai, Yu-Sheng
Abstract : A simple structure, efficient color splitting, sufficient output of electrical signals, and low power consumption are the important characteristics of contemporary devices for color sensing. Abstract : A simple structure, efficient color splitting, sufficient output of electrical signals, and low power consumption are the important characteristics of contemporary devices for color sensing. In this study, we developed filter-free, junctionless structures that exhibited a superior photo-thermo-electrical response under a low bias voltage and a short response time in milliseconds. Although our compact sensor had a simple single-layer trench-like aluminum (Al) structure, it could perform multiple functions, including light harvesting, color-selective absorption, photo-thermo-electrical transformation, and the ability to collect photoinduced differences in electrical signals. This device exploited near-field surface plasmon resonance and cavity effects to enhance the intensity of the electric field and the color-selective absorption, ultimately resulting in significant current signals in its structured Al film. This strategy significantly simplifies not only the components of the color sensor but also its fabrication; for example, red, green, and blue color detection devices could be prepared simultaneously through a single lithography, etching, and deposition step. With its ability to provide functional filter-free, junctionless structures, this strategy has great potential for the production of devices that operate on different kinds of substrates, thereby bridging various applications of color sensing technologies.